BATIK DERMAYON SUATU KEINDAHAN DALAM SEBUAH KETERBATASAN - Muh. Arif Jati Purnomo (Pendhapa, 2011)
IndramayuÂ batik or people used to call the Dermayon batik is one of the coastal batik that had its own uniqueness and beauty of the coastal batik among others. One hallmark of this Dermayon batik is the emergence of technique "cocohan" on some batik fabric. Technique "cocohan" is a technique for making â€œisen-isenâ€ of batik that form "cecek" or dots using â€œcomplonganâ€ tool. It is made of wood that there is a lot of nails at the bottom that used to pierce the layers of wax (malam) that has been attached to the fabric. â€œCocohanâ€ technique is emerging as a creative effort of batik paintings who incidentally are the fisherman's wife who tries to find an additional income while waiting for their husbands come home from fishing. From the limited time available to make a piece of batik cloth, then comes the staining technique â€œcocohanâ€ with a very minimalist but capable of producing batik works of unique and interesting.Keywords:Â Dermayon batik, â€œcocohanâ€